Community Governance for Coastal Empowerment in Bintan Regency: Challenges and Strategies - Alfiandri, Alfiandri; Rivai, Nur Ilmiah; Darmawan, Eki; Irawan, Bambang (Universitas Padjadjaran, 2024)
This study explores community governance within the context of coastal community empowerment policies in Bintan Regency. The research employed a qualitative approach, utilizing in-depth interviews and participatory observation to collect data. The findings indicate that community governance plays a central role in the empowerment policies, characterized by active community participation in decision-making and the implementation of empowerment programs. However, the study also identifies challenges, such as conflicts of interest among stakeholders, limited private sector involvement, and insufficient understanding of community roles in the empowerment process. To address these issues, collaboration between the government, community, and private sector is crucial to foster an environment conducive to sustainable and effective community governance. The research further emphasizes the importance of social institutions, such as non-governmental organizations, traditional institutions, and religious organizations, in strengthening community participation. The findings aim to enhance the understanding of community governance's significance in coastal community empowerment policies and provide policy recommendations to improve its effectiveness in Bintan Regency.